Interactions of dendritic glycopolymer with erythrocytes, red blood cell ghosts and membrane enzymes - Wrobel, Dominika; Janaszewska, Anna; Appelhans, Dietmar; Voit, Brigitte; Bryszewska, Maria; Maly, Jan (International Journal of Pharmaceutics, 2015)
Interactions between maltose functionalized hyperbranched poly(ethylene imine)s (95% maltose decoration denoted as Mal-PEI A; 33% maltose decoration denoted as Mal-PEI B) and red blood cells (RBCs) and between red blood cell membranes were investigated. We monitored the degree of hemolysis, the change in cell shape, the influence of polymers on the fluidity of the cell membrane and some cell membrane enzymes to determine their possible cytotoxic impact on them. To observe the extent of hemolysis, the RBCs were incubated with different concentrations of Mal-PEIs. The first significant lysis of RBCs was observed after 6 h of incubation. Prolongation of the incubation time increased the number of ruptured cells. Moreover, we observed that Mal-PEI B was more hemolytic than Mal-PEI A in buffer solution. In contrast, an incubation of RBCs with Mal-PEIs in human plasma significantly decreased the hemolytic process and showed higher hemolytic property of Mal-PEI A compared to Mal-PEI B. Also several changes in the shape of the RBCs occurred after incubation with Mal-PEIs. Some of the erythrocytes shrank (echinocytes), but their morphology generally remained unchanged during the incubation. As shown by fluorescence experiments, both polymers induced the increase of fluidity of RBCs membranes. In summary, both types of hyperbranched poly(ethylene imine)s were practically non-hemolytic even at high polymer concentrations. Mal-PEI B was slightly more noxious than the Mal-PEI A in a buffer solution, while in blood plasma, the situation was opposite. Decrease of Na+/K+ ATPase and total ATPase enzymes activity was related with molecule size and number of maltose groups on the surface of molecule. The low hemolytic properties only observed at higher concentration (100 μM and 400 μM) indicated that Mal-PEIs are promising macromolecules in the area of drug delivery systems.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Dendritic glycopolymer; Erythrocytes; Hemolysis; Nanoparticles